Nickel-zinc secondary battery negative electrode plate and nickel-zinc secondary battery
By adding chopped fibers to the negative electrode material of the negative electrode sheet of the nickel-zinc secondary battery, the problem of peeling and spontaneous dissolution of the negative electrode material is solved, and the storage performance and cycle life of the battery are improved.
Patent Information
- Application Number
- CN202411377809.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-09-30
AI Technical Summary
The negative electrode material of the negative electrode sheet of the aqueous nickel-zinc secondary battery is easily peeled off the substrate and spontaneously dissolved in the aqueous alkaline electrolyte, resulting in poor storage and cycle life performance of the battery cell.
The negative electrode material using the negative electrode sheet includes negative active substances, surfactants, binders and chopped fibers. The fiber length of the chopped fibers is 0.1mm-2mm and the mass percentage is 1%-4% to strengthen the negative electrode. The toughness and strength of the electrode piece prevent the negative electrode material from peeling off and spontaneous dissolution.
It effectively prevents the peeling and spontaneous dissolution of negative electrode materials, improves current distribution, and improves the long-term storage performance and cycle life performance of nickel-zinc secondary batteries.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of nickel-zinc batteries, and in particular to a negative electrode sheet of a nickel-zinc secondary battery and a nickel-zinc secondary battery. Background Art
[0002] The rapid depletion of fossil fuel resources and the related worsening environmental pollution are critical and challenging energy and environmental issues, and are one of the most important research hotspots in the 21st century. In recent years, with the increasing application of lithium-ion batteries in energy storage devices, fire accidents caused by lithium-ion batteries have become more and more frequent, attracting widespread attention. Aqueous nickel-zinc secondary batteries have the advantages of low cost, high safety, abundant natural zinc resources, and high weight energy density, making aqueous nickel-zinc secondary batteries a promising candidate for alleviating current energy and environmental problems, and playing an important role in green and safe power sources.
[0003] The safety of aqueous electrolytes of aqueous nickel-zinc secondary batteries, as well as their excellent rate performance and environmental friendliness, make aqueous nickel-zinc secondary batteries stand out and receive widespread attention. However, the negative electrode material of the negative electrode plate of aqueous nickel-zinc secondary batteries in related technologies is easily peeled off the matrix and spontaneously dissolves in the aqueous alkaline electrolyte, causing the negative electrode active substance of the negative electrode material to undergo hydrogen evolution reaction, zinc dendrite growth and zinc deformation in the alkaline electrolyte, resulting in poor long-term storage performance and cycle life performance of the battery cell, hindering the application of nickel-zinc secondary batteries. Summary of the invention
[0004] In order to solve or partially solve the problems existing in the related art, the present application provides a nickel-zinc secondary battery negative electrode sheet and a nickel-zinc secondary battery, which can effectively prevent the negative electrode material of the nickel-zinc secondary battery negative electrode sheet from peeling off the negative electrode matrix, inhibit the spontaneous dissolution of the negative electrode material in the electrolyte, take into account the long-term storage performance and cycle life performance of the nickel-zinc secondary battery, and improve the long-term storage performance and cycle life performance of the nickel-zinc secondary battery.
[0005] The first aspect of the present application provides a negative electrode plate for a nickel-zinc secondary battery, wherein the negative electrode plate for the nickel-zinc secondary battery comprises a negative electrode substrate and a negative electrode material coated on the negative electrode substrate; wherein:
[0006] The negative electrode material comprises a negative electrode active material, a surfactant, a binder, and chopped fibers; the fiber length of the chopped fibers is 0.1 mm-2 mm, and the mass percentage of the chopped fibers in the negative electrode material is 1%-4%.
[0007] Preferably, the chopped fibers include chopped aluminum silicate fibers, and the mass percentage of the chopped aluminum silicate fibers in the negative electrode material is 1%-3%.
[0008] Preferably, the chemical formula of the aluminum silicate of the chopped aluminum silicate fiber is Al X Si Y O (3 / 2X+2Y) Or XAl2O3·YSiO2, where 0 <Y≤X。
[0009] Preferably, the ratio of X to Y is X:Y=1:1, or 4:1, or 3:2.
[0010] Preferably, the chopped fibers further include chopped carbon conductive fibers, and the mass percentage of the chopped carbon conductive fibers in the negative electrode material is 1%-2%.
[0011] Preferably, the chopped fibers have a fiber length of 0.1 mm to 1 mm.
[0012] Preferably, the fiber diameter of the chopped fibers is 10 μm-20 μm.
[0013] Preferably, the negative electrode material further includes additives, the additives include Ca(OH)2, Bi2O3, In2O3; the negative electrode active material includes spherical ZnO powder and Zn nanopowder; wherein,
[0014] The mass percentage of the spherical ZnO powder in the negative electrode material is 55%-60%;
[0015] The mass percentage of the Zn nanopowder in the negative electrode material is 5%-10%;
[0016] The mass percentage of Ca(OH)2 in the negative electrode material is 1%-1.5%;
[0017] The mass percentage of Bi2O3 in the negative electrode material is 0.5%-2%;
[0018] The mass percentage of In2O3 in the negative electrode material is 0.05%-0.08%.
[0019] Preferably, the negative electrode substrate is a copper-tinned inclined wire mesh substrate.
[0020] A second aspect of the present application provides a nickel-zinc secondary battery, which includes a positive electrode plate, a separator, and the nickel-zinc secondary battery negative electrode plate as described above.
[0021] The technical solution provided by this application may have the following beneficial effects:
[0022] According to the technical solution of the present application, the negative electrode sheet of the nickel-zinc secondary battery includes a negative electrode substrate and a negative electrode material coated on the negative electrode substrate, the negative electrode material includes a negative electrode active substance, a surfactant, a binder, and chopped fibers, wherein the fiber length of the chopped fibers is 0.1 mm-2 mm, and the mass percentage of the chopped fibers in the negative electrode material is 1%-4%; the chopped fibers of the negative electrode material can enhance the toughness and strength of the negative electrode sheet, prevent the negative electrode material from loosening and falling off, and make the negative electrode material tightly attached to the negative electrode substrate, and can effectively prevent the negative electrode material from peeling off the negative electrode substrate, inhibit the spontaneous dissolution of the negative electrode material in an aqueous alkaline electrolyte, inhibit the hydrogen evolution reaction and the generation of zinc dendrites of the negative electrode active substance of the negative electrode material in the alkaline electrolyte, improve the current distribution of the negative electrode sheet, make the current distribution of the negative electrode sheet more uniform, take into account the long-term storage performance and cycle life performance of the nickel-zinc secondary battery, and improve the long-term storage performance and cycle life performance of the nickel-zinc secondary battery.
[0023] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. DETAILED DESCRIPTION
[0024] The terms used in this application are for the purpose of describing specific embodiments only and are not intended to limit this application. The singular forms of "a", "said" and "the" used in this application and the appended claims are also intended to include plural forms unless the context clearly indicates other meanings. It should also be understood that the term "and / or" used herein refers to and includes any or all possible combinations of one or more associated listed items.
[0025] It should be understood that although the terms "first", "second", "third", etc. may be used in this application to describe various information, this information should not be limited to these terms. These terms are only used to distinguish the same type of information from each other. For example, without departing from the scope of this application, the first information may also be referred to as the second information, and similarly, the second information may also be referred to as the first information. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of this application, the meaning of "multiple" is two or more, unless otherwise clearly and specifically defined.
[0026] The embodiment of the present application provides a negative electrode plate for a nickel-zinc secondary battery, which can effectively prevent the negative electrode material of the negative electrode plate for the nickel-zinc secondary battery from peeling off the negative electrode matrix, inhibit the spontaneous dissolution of the negative electrode material in the electrolyte, take into account the long-term storage performance and cycle life performance of the nickel-zinc secondary battery, and improve the long-term storage performance and cycle life performance of the nickel-zinc secondary battery.
[0027] The technical solutions of the embodiments of the present application are described in detail below.
[0028] An embodiment of the present application provides a negative electrode plate for a nickel-zinc secondary battery, which includes a negative electrode substrate and a negative electrode material coated on the negative electrode substrate; wherein the negative electrode material includes a negative electrode active substance, a surfactant, a binder, and chopped fibers, the fiber length of the chopped fibers is 0.1 mm (millimeter) - 2 mm, and the mass percentage of the chopped fibers in the negative electrode material is 1%-4%.
[0029] The negative electrode sheet of the nickel-zinc secondary battery in the embodiment of the present application, the negative electrode material coated on the negative electrode substrate includes a negative electrode active substance, a surfactant, a binder, and chopped fibers, wherein the fiber length of the chopped fibers is 0.1 mm-2 mm, and the mass percentage of the chopped fibers in the negative electrode material is 1%-4%; the chopped fibers of the negative electrode material can enhance the toughness and strength of the negative electrode sheet, prevent the negative electrode material from loosening and falling off, and make the negative electrode material tightly attached to the negative electrode substrate, and can effectively prevent the negative electrode material from peeling off the negative electrode substrate, inhibit the spontaneous dissolution of the negative electrode material in the aqueous alkaline electrolyte, inhibit the hydrogen evolution reaction and the generation of zinc dendrites of the negative electrode active substance of the negative electrode material in the alkaline electrolyte, improve the current distribution of the negative electrode sheet, make the current distribution of the negative electrode sheet more uniform, take into account the long-term storage performance and cycle life performance of the nickel-zinc secondary battery, and improve the long-term storage performance and cycle life performance of the nickel-zinc secondary battery.
[0030] The negative electrode plate of the nickel-zinc secondary battery in the embodiment of the present application comprises a negative electrode substrate and a negative electrode material coated on the negative electrode substrate; wherein the negative electrode material comprises a negative electrode active substance, an additive, a surfactant, a binder, and chopped fibers, the fiber length of the chopped fibers is 0.1 mm-2 mm, and the mass percentage of the chopped fibers in the negative electrode material is 1%-4%.
[0031] In one embodiment, the negative electrode active material may include spherical ZnO (zinc oxide) powder or Zn (zinc) nanopowder.
[0032] In one embodiment, the additive includes Ca(OH) 2 (calcium hydroxide), Bi 2 O 3 (bismuth trioxide), and In 2 O 3 (indium trioxide).
[0033] In one embodiment, the chopped fibers include chopped aluminum silicate fibers, and the mass percentage of the chopped aluminum silicate fibers in the negative electrode material is 1%-3%.
[0034] In one embodiment, the chemical formula of aluminum silicate in the chopped aluminum silicate fibers is Al X Si Y O (3 / 2X+2Y) Or XAl2O3·YSiO2, where 0 <Y≤X。
[0035] In one embodiment, the ratio of X to Y is X:Y=1:1, or 4:1, or 3:2.
[0036] In one embodiment, the negative electrode material of the negative electrode plate may include 55wt%-60wt% spherical ZnO powder, 5wt%-10wt% Zn nanopowder, 1wt%-1.5wt% Ca(OH)2, 0.5wt%-2wt% Bi2O3, 0.05wt%-0.08wt% In2O3, 0.01wt%-0.5wt% anionic surfactant, 25wt%-30wt% binder, 1wt%-3wt% chopped aluminum silicate fiber. Add an appropriate amount of pure water to the negative electrode material, stir and mix evenly to obtain a uniform negative electrode slurry; apply the negative electrode slurry to the negative electrode substrate by a paste coating method, compound the negative electrode slurry with the negative electrode substrate, and then dry, roll, soften, and cut to obtain a negative electrode plate of a nickel-zinc secondary battery of suitable size.
[0037] In one embodiment, the fiber length of the chopped aluminum silicate fibers is 0.1 mm (millimeter) to 1 mm.
[0038] In one embodiment, the fiber diameter of the chopped aluminum silicate fibers is 10 μm (micrometers) to 20 μm.
[0039] In one embodiment, the chopped fibers further include chopped carbon conductive fibers, and the mass percentage of the chopped carbon conductive fibers is 1%-2%.
[0040] In one embodiment, the negative electrode material of the negative electrode plate may include 55wt%-60wt% spherical ZnO powder, 5wt%-10wt% Zn nanopowder, 1wt%-1.5wt% Ca(OH)2, 0.5wt%-2wt% Bi2O3, 0.05wt%-0.08wt% In2O3, 0.01wt%-0.5wt% anionic surfactant, 25wt%-30wt% binder, 1wt%-3wt% chopped aluminum silicate fiber, 1wt%-2wt% chopped carbon conductive fiber. Add an appropriate amount of pure water to the negative electrode material, stir and mix evenly to obtain a uniform negative electrode slurry; apply the negative electrode slurry to the negative electrode substrate by a paste coating method, compound the negative electrode slurry with the negative electrode substrate, and then dry, roll, soften, and cut to obtain a negative electrode plate of a nickel-zinc secondary battery of suitable size.
[0041] In one embodiment, the fiber length of the chopped carbon conductive fibers is 0.1 mm-1 mm.
[0042] In one embodiment, the fiber diameter of the chopped carbon conductive fibers is 10 μm-20 μm.
[0043] In one embodiment, the surfactant may be an anionic surfactant, and the anionic surfactant may be sodium dodecylbenzene cyclate and / or sodium dodecylbenzene sulfonate.
[0044] In one embodiment, the binder may be one or more selected from carboxymethyl cellulose (CMC), styrene-butadiene rubber, and polytetrafluoroethylene (PTFE). The binder can bond the negative electrode materials to each other, disperse and suspend the negative electrode materials in the negative electrode slurry, increase or decrease the viscosity of the negative electrode slurry, and adjust the viscosity of the negative electrode slurry.
[0045] In one embodiment, during the preparation of the negative electrode slurry, a binder solid powder may be added to pure water, and a binder aqueous solution with a set mass percentage may be prepared by mechanical stirring; the binder aqueous solution and other materials of the negative electrode material may be stirred evenly to prepare the negative electrode slurry. For example, a CMC aqueous solution with a CMC mass percentage of 2% may be stirred evenly with other materials of the negative electrode material to prepare the negative electrode slurry; wherein the CMC aqueous solution with a CMC mass percentage of 2% refers to a solution containing 2 grams of CMC solid powder in 100 grams of CMC aqueous solution.
[0046] The negative electrode sheet of the nickel-zinc secondary battery of the embodiment of the present application, the negative electrode material coated on the negative electrode substrate includes a negative electrode active substance, a surfactant, a binder, and chopped fibers; the chopped fibers include chopped aluminum silicate fibers, wherein the mass percentage of the chopped aluminum silicate fibers in the negative electrode material is 1%-3%, and the fiber length is 0.1mm-2mm. The slender chopped aluminum silicate fibers can make the negative electrode active substances bond together, so that the negative electrode active substances are compact and not easy to separate from the negative electrode active substances, and can enhance the toughness and strength of the negative electrode sheet, avoid the loosening and falling of the negative electrode material, make the negative electrode material closely attached to the negative electrode substrate, and effectively prevent the negative electrode material from peeling off the negative electrode substrate. The chopped aluminum silicate fibers can effectively confine aluminum and silicon elements to the negative electrode sheet, and aluminum silicate can react with the electrolyte, reducing the negative electrode active substance and the electrolyte. The chopped aluminum silicate fibers are slightly soluble in a strong alkaline environment. The precipitated aluminum and silicon can form a protective film on the surface of the electrode, which can inhibit the spontaneous dissolution of the negative electrode material in the aqueous alkaline electrolyte, inhibit the side reaction of the negative electrode active substance, inhibit the hydrogen evolution reaction of the negative electrode active substance in the alkaline electrolyte and the formation of zinc dendrites, improve the current distribution of the negative electrode sheet, take into account the long-term storage performance and cycle life performance of the nickel-zinc secondary battery, and improve the long-term storage performance and cycle life performance of the nickel-zinc secondary battery.
[0047] Furthermore, in the negative electrode sheet of the nickel-zinc secondary battery of the embodiment of the present application, the negative electrode material coated on the negative electrode substrate includes a negative electrode active substance, a surfactant, a binder, and chopped fibers; the chopped fibers include chopped aluminum silicate fibers and chopped carbon conductive fibers, and the chopped aluminum silicate fibers and chopped carbon conductive fibers can enhance the toughness and strength of the negative electrode sheet, prevent the negative electrode material from loosening and falling off, and make the negative electrode material closely attached to the negative electrode substrate, which can effectively prevent the negative electrode material from peeling off the negative electrode substrate, and the chopped aluminum silicate fibers can effectively confine aluminum and silicon elements in the negative electrode. The electrode sheet can inhibit the spontaneous dissolution of the negative electrode material in the aqueous alkaline electrolyte, inhibit the hydrogen evolution reaction of the negative electrode active substance of the negative electrode material in the alkaline electrolyte and the generation of zinc dendrites; at the same time, the short-cut carbon conductive fiber can be used as a conductive material to construct a conductive network of the electrode sheet, improve the current distribution of the negative electrode sheet, make the current distribution of the negative electrode sheet more uniform, solve the problem of uneven current of the negative electrode sheet caused by zinc dendrites, take into account the long-term storage performance and cycle life performance of the nickel-zinc secondary battery, and improve the long-term storage performance and cycle life performance of the nickel-zinc secondary battery.
[0048] Furthermore, in the negative electrode plate of the nickel-zinc secondary battery of the embodiment of the present application, the negative electrode active material includes spherical ZnO powder and Zn nanopowder; the additives include Ca(OH)2, Bi2O3, and In2O3; the spherical ZnO powder is a form of ZnO with the largest specific surface area, which is beneficial to increase the contact area of the reaction. 55wt%-60wt% of the spherical ZnO powder and 5wt%-10wt% of the Zn nanopowder can reduce the proportion of zinc to reduce the occurrence of side reactions between zinc and alkaline electrolyte, and can ensure the overall negative electrode of the nickel-zinc secondary battery. To maximize the capacity; the additive Ca (OH) 2 can react with the negative electrode ZnO in an alkaline environment to form calcium zincate, which can inhibit the dissolution of ZnO and the formation of a zinc deposition passivation layer; the additives Bi2O3 and In2O3 can build a conductive network for the electrode, optimize the negative electrode current during the battery charge and discharge process, and make the current of the negative electrode evenly distributed during the battery charge and discharge process. At the same time, Bi2O3 will adhere to the surface of the electrode after being reduced, inhibiting the corrosion of zinc, and can recombine the oxygen generated by the positive electrode and the hydrogen generated by the negative electrode to relieve the internal air pressure of the battery cell.
[0049] Furthermore, in the negative electrode plate of the nickel-zinc secondary battery in the embodiment of the present application, the anionic surfactant of the negative electrode material can inhibit zinc corrosion and passivation, and can form a fluffy protective layer on the surface of the negative electrode plate in the negative electrode system. The fluffy protective layer can provide a channel for ion transfer at the solid-liquid interface and can slow down the reaction between the negative electrode zinc and zinc oxide and the alkaline electrolyte.
[0050] In addition, an embodiment of the present application further provides a nickel-zinc secondary battery, which includes a positive electrode plate, a separator, and the above-mentioned nickel-zinc secondary battery negative electrode plate.
[0051] In one embodiment, the positive electrode material of the positive electrode plate can be mixed with an appropriate amount of pure water to prepare a positive electrode slurry; the positive electrode slurry is applied to a surface density of 250 g / m 2 (grams per square meter) -380g / m 2 The positive electrode current collector (for example, the positive electrode current collector is foamed nickel) is prepared, and the positive electrode slurry is compounded with the positive electrode current collector to obtain a positive electrode sheet of a nickel-zinc secondary battery.
[0052] In one embodiment, the positive electrode slurry of the nickel-zinc secondary battery includes 70wt%-75wt% of spherical β-Ni(OH)2 (nickel hydroxide) with a surface coated with trivalent cobalt, 0.01wt%-0.05wt% of Ca(OH)2 (calcium hydroxide), 3wt%-4wt% of a conductive agent, 0.5wt%-1wt% of Y2O3 (yttrium trioxide) or 0.5wt%-1wt% of Yb2O3 (ytterbium trioxide), 2wt%-3wt% of a binder, 1wt%-2wt% of a suspending agent, and the remainder is pure water.
[0053] In one embodiment, the conductive agent can be selected from one or more of Cu (copper), Ni (nickel), and Zn (zinc). In a specific embodiment, the conductive agent has a particle size of 1 μm (micrometer) to 3 μm and a tap density of 1 g / cm 3 (grams per cubic centimeter) -3g / cm 3 Ni powder.
[0054] In a specific embodiment, the binder having a dispersing and binding effect can be prepared by first preparing a binder aqueous solution when preparing the positive electrode slurry; then the binder aqueous solution and other materials of the positive electrode material are stirred evenly to prepare the positive electrode slurry. In a specific embodiment, the binder aqueous solution can be a CMC aqueous solution and / or a PTFE aqueous solution. The CMC aqueous solution can be a CMC aqueous solution with a CMC mass percentage of 2%. The PTFE aqueous solution can be a PTFE aqueous solution with a PTFE mass percentage of 60%. In a specific embodiment, a polytetrafluoroethylene solid powder and pure water with a mass ratio of 3:2 can be fully stirred evenly by a magnetic stirrer to obtain a 60% wt PTFE aqueous solution.
[0055] In a specific embodiment, the spherical β-Ni(OH)2 with trivalent cobalt on the surface of the active material and the conductive nickel powder have relatively high density. When the positive electrode slurry is left standing, the high-density substances will sink to the bottom. Adding the suspending agent xanthan gum to the positive electrode slurry can avoid the sinking of high-density substances when the positive electrode slurry is left standing.
[0056] In one embodiment, the diaphragm of the nickel-zinc secondary battery can absorb alkali solution and insulate to prevent short circuit, and adopts a layer of non-woven fabric and three layers of PE (Polyethylene) anti-dendrite composite diaphragm, or a layer of non-woven fabric and three layers of PP (Polypropylene) anti-dendrite composite diaphragm. The alkali-absorbing non-woven fabric facing the positive electrode plate is hydrophilicized by sulfonation or grafting, and the three-layer PE microporous diaphragm or three-layer PP microporous diaphragm facing the negative electrode plate is hydrophilicized by sulfonation or grafting.
[0057] In one embodiment, the electrolyte of the nickel-zinc secondary battery may be one or more of KOH (potassium hydroxide), NaOH (sodium hydroxide), LiOH (lithium hydroxide), Al(OH) 3 (aluminum hydroxide), and Zn(OH) 2 (zinc hydroxide).
[0058] In one embodiment, the electrolyte may further include 0.3 mol / L-1 mol / L ZnO to inhibit the dissolution of the negative electrode material in the electrolyte.
[0059] In one embodiment, the electrolyte may further include a buffer, and the buffer may be phosphate.
[0060] In one embodiment, the pH value of the electrolyte is 10-14 at 25 degrees Celsius, and the conductivity is 350 mS / cm (milliSiemens per centimeter)-470 mS / cm. In order to improve the cycle performance of the nickel-zinc secondary battery of the embodiment of the present application, the amount of electrolyte injected is 1 / 5 of the weight of the positive electrode sheet and the negative electrode sheet.
[0061] The invention is further described below by means of specific Examples 1-18 and Comparative Examples.
[0062] According to the 2A1500 battery cell design and the above-mentioned nickel-zinc secondary battery negative electrode sheet, positive electrode sheet, separator and electrolyte, the nickel-zinc secondary batteries corresponding to Examples 1-18 and the comparative example were prepared respectively; wherein,
[0063] In the comparative example, the negative electrode material of the negative electrode plate does not contain chopped aluminum silicate fibers and chopped carbon conductive fibers, and the mass percentage of the chopped aluminum silicate fibers and the chopped carbon conductive fibers is 0.
[0064] In Example 1, the mass percentage of the chopped aluminum silicate fibers in the negative electrode material of the negative electrode plate is 1%, the ratio of the chemical formula X to Y of aluminum silicate is X:Y=3:2, and the fiber length of the chopped aluminum silicate fibers is 1 mm.
[0065] In Example 2, the mass percentage of the chopped aluminum silicate fibers in the negative electrode material of the negative electrode plate is 2%, the ratio of the chemical formula X to Y of aluminum silicate is X:Y=3:2, and the fiber length of the chopped aluminum silicate fibers is 1 mm.
[0066] In Example 3, the mass percentage of the chopped aluminum silicate fibers in the negative electrode material of the negative electrode plate is 3%, the ratio of the chemical formula X to Y of aluminum silicate is X:Y=3:2, and the fiber length of the chopped aluminum silicate fibers is 1 mm.
[0067] In Example 4, the mass percentage of chopped aluminum silicate fibers in the negative electrode material of the negative electrode plate is 3%, the mass percentage of chopped carbon conductive fibers is 1%, the ratio of the chemical formula X to Y of aluminum silicate is X:Y=3:2, the fiber length of the chopped aluminum silicate fibers is 1 mm, and the fiber length of the chopped carbon conductive fibers is 1 mm.
[0068] In Example 5, the mass percentage of chopped aluminum silicate fibers in the negative electrode material of the negative electrode plate is 3%, the mass percentage of chopped carbon conductive fibers is 2%, the ratio of the chemical formula X to Y of aluminum silicate is X:Y=3:2, the fiber length of the chopped aluminum silicate fibers is 1 mm, and the fiber length of the chopped carbon conductive fibers is 1 mm.
[0069] In Example 6, the mass percentage of the chopped aluminum silicate fibers in the negative electrode material of the negative electrode plate is 0.5%, the ratio of the chemical formula X to Y of aluminum silicate is X:Y=3:2, and the fiber length of the chopped aluminum silicate fibers is 1 mm.
[0070] In Example 7, the mass percentage of the chopped aluminum silicate fibers in the negative electrode material of the negative electrode plate is 4%, the ratio of the chemical formula X to Y of aluminum silicate is X:Y=3:2, and the fiber length of the chopped aluminum silicate fibers is 1 mm.
[0071] In Example 8, the mass percentage of chopped aluminum silicate fibers in the negative electrode material of the negative electrode plate is 3%, the mass percentage of chopped carbon conductive fibers is 1%, the ratio of the chemical formula X to Y of aluminum silicate is X:Y=4:1, the fiber length of the chopped aluminum silicate fibers is 1 mm, and the fiber length of the chopped carbon conductive fibers is 1 mm.
[0072] In Example 9, the mass percentage of chopped aluminum silicate fibers in the negative electrode material of the negative electrode plate is 3%, the mass percentage of chopped carbon conductive fibers is 1%, the ratio of the chemical formula X to Y of aluminum silicate is X:Y=1:1, the fiber length of the chopped aluminum silicate fibers is 1 mm, and the fiber length of the chopped carbon conductive fibers is 1 mm.
[0073] In Example 10, the mass percentage of chopped aluminum silicate fibers in the negative electrode material of the negative electrode plate is 3%, the mass percentage of chopped carbon conductive fibers is 0.5%, the ratio of the chemical formula X to Y of aluminum silicate is X:Y=3:2, the fiber length of the chopped aluminum silicate fibers is 1 mm, and the fiber length of the chopped carbon conductive fibers is 1 mm.
[0074] In Example 11, the mass percentage of chopped aluminum silicate fibers in the negative electrode material of the negative electrode plate is 3%, the mass percentage of chopped carbon conductive fibers is 2.5%, the ratio of the chemical formula X to Y of aluminum silicate is X:Y=3:2, the fiber length of the chopped aluminum silicate fibers is 1 mm, and the fiber length of the chopped carbon conductive fibers is 1 mm.
[0075] In Example 12, the mass percentage of the chopped carbon conductive fibers in the negative electrode material of the negative electrode plate is 1%, and the fiber length of the chopped carbon conductive fibers is 1 mm.
[0076] In Example 13, the mass percentage of the chopped carbon conductive fibers in the negative electrode material of the negative electrode plate is 2%, and the fiber length of the chopped carbon conductive fibers is 1 mm.
[0077] In Example 14, the mass percentage of chopped aluminum silicate fibers in the negative electrode material of the negative electrode plate is 2%, the mass percentage of chopped carbon conductive fibers is 2%, the ratio of the chemical formula X to Y of aluminum silicate is X:Y=3:2, the fiber length of the chopped aluminum silicate fibers is 0.05 mm, and the fiber length of the chopped carbon conductive fibers is 0.05 mm.
[0078] In Example 15, the mass percentage of chopped aluminum silicate fibers in the negative electrode material of the negative electrode plate is 2%, the mass percentage of chopped carbon conductive fibers is 2%, the ratio of the chemical formula X to Y of aluminum silicate is X:Y=3:2, the fiber length of the chopped aluminum silicate fibers is 0.1 mm, and the fiber length of the chopped carbon conductive fibers is 0.1 mm.
[0079] In Example 16, the mass percentage of chopped aluminum silicate fibers in the negative electrode material of the negative electrode plate is 2%, the mass percentage of chopped carbon conductive fibers is 2%, the ratio of the chemical formula X to Y of aluminum silicate is X:Y=3:2, and the fiber length of the chopped aluminum silicate fibers and the chopped carbon conductive fibers is 0.5 mm.
[0080] In Example 17, the mass percentage of chopped aluminum silicate fibers in the negative electrode material of the negative electrode plate is 2%, the mass percentage of chopped carbon conductive fibers is 2%, the ratio of the chemical formula X to Y of aluminum silicate is X:Y=3:2, and the fiber length of the chopped aluminum silicate fibers and the chopped carbon conductive fibers is 1.0 mm.
[0081] In Example 18, the mass percentage of chopped aluminum silicate fibers in the negative electrode material of the negative electrode plate is 2%, the mass percentage of chopped carbon conductive fibers is 2%, the ratio of the chemical formula X to Y of aluminum silicate is X:Y=3:2, and the fiber length of the chopped aluminum silicate fibers and the chopped carbon conductive fibers is 2.0 mm.
[0082] The positive electrode sheet, negative electrode sheet and separator of Examples 1-18 and the comparative example are wound in a winding manner of wrapping the negative electrode sheet. The positive electrode sheet, negative electrode sheet and separator of Examples 1-18 and the comparative example are obtained by winding. Among them, the positive electrode is connected to the positive electrode cap, and the negative electrode is in contact with the steel shell. The positive electrode ear is made of pure nickel. In order to prevent the zinc in the negative electrode sheet and the iron element in the steel shell from forming a micro-battery and causing side reactions, a layer of tin-plated copper foil slightly wider than the negative electrode sheet, with a total thickness of 0.03 mm (millimeter) and a tin-plated layer thickness of 5 μm is wrapped around the outermost side of the battery electrode group.
[0083] After the nickel-zinc secondary batteries corresponding to Examples 1-18 and the comparative examples were manufactured, the actual capacities were confirmed by formation. According to the actual capacities, the nickel-zinc secondary batteries corresponding to Examples 1-18 and the comparative examples were subjected to accelerated tests of 70°C (degrees Celsius) high-temperature storage test and 1C charge-discharge cycle test, respectively, to obtain the test results shown in Tables 1-5.
[0084] The 70℃ high-temperature storage test is to place the fully charged battery in a 70℃ constant temperature oven, take out three batteries every 5 days, and discharge them after the batteries have cooled to the room temperature of 25℃. The discharge amount divided by the actual capacity before placement is recorded as SOC (state of charge, used to reflect the remaining capacity of the battery), and the SOC of the three batteries is then averaged; 1C charging and discharging is based on the actual capacity of the battery. For example, if the actual capacity of the battery is 1460mAh, both charging and discharging are set to 1460mAh cutoff.
[0085] At a constant temperature of 25°C, the standard capacity CIEC is obtained by charging and discharging at 0.2C, and the discharge capacities CnC at different discharge rates of 1C, 3C, 5C, and 10C are obtained respectively. Taking the standard capacity CIEC as the benchmark (100%), the discharge capacity SOCnC at different rates is calculated, where SOCnC=CnC / CIEC, nC is the discharge rate of 1C, 3C, 5C, and 10C, and the discharge test data at different rates (1C, 3C, 5C, and 10C) are obtained as shown in Tables 1 and 2.
[0086] Table 1:
[0087]
[0088] Table 2
[0089]
[0090] Table 3
[0091]
[0092] Table 4
[0093]
[0094] Table 5
[0095]
[0096] According to the 5-day-SOC, 10-day-SOC, 15-day-SOC and 150cyc-SOH (battery health status of 150 cycles) of the comparative examples in Table 1 and Table 2 and Examples 1-3 and Examples 6-7, the cycle life performance and the long-term storage performance in the high-temperature storage test of the nickel-zinc secondary battery are significantly improved. It can be seen that the addition of short-cut aluminum silicate fibers to the negative electrode material can make the negative electrode active materials bonded to each other, making the negative electrode active materials compact and not easy to separate from the negative electrode active materials, which can enhance the toughness and strength of the negative electrode sheet, avoid the loosening and falling of the negative electrode material, make the negative electrode material closely attached to the negative electrode matrix, and effectively prevent the negative electrode material from falling off. The material is stripped of the negative electrode matrix, and the short-cut aluminum silicate fiber can effectively confine the aluminum and silicon elements to the negative electrode plate, and the aluminum silicate can react with the electrolyte, reducing the reaction of the negative electrode active substance with the electrolyte. The short-cut aluminum silicate fiber is slightly soluble in a strong alkaline environment, and the precipitated aluminum and silicon can form a protective film on the surface of the plate, which can inhibit the spontaneous dissolution of the negative electrode material in the aqueous alkaline electrolyte, inhibit the side reaction of the negative electrode active substance, inhibit the hydrogen evolution reaction of the negative electrode active substance of the negative electrode material in the alkaline electrolyte and the formation of zinc dendrites, improve the current distribution of the negative electrode plate, take into account the long-term storage performance and cycle life performance of the nickel-zinc secondary battery, and improve the long-term storage performance and cycle life performance of the nickel-zinc secondary battery.
[0097] According to the comparative example in Table 1 and the 5-day-SOC, 10-day-SOC, 15-day-SOC and 150cyc-SOH of Examples 4-5, by adding chopped aluminum silicate fibers and chopped carbon conductive fibers to the negative electrode material, the cycle life performance of the nickel-zinc secondary battery and the long-term storage performance in the high-temperature storage test are also significantly improved. It can be seen that by adding chopped aluminum silicate fibers and chopped carbon conductive fibers to the negative electrode material, the dissolution and shedding of the negative electrode material in the alkaline electrolyte is greatly slowed down, and the Si element and the Al element inhibit the corrosion of the negative electrode active material, thereby improving the self-discharge performance of the battery cell. The added chopped carbon conductive fibers further improve the cycle life performance of the battery cell. The evenly dispersed chopped carbon conductive fibers play the role of building a conductive network in the negative electrode sheet, improving the current distribution of the negative electrode sheet, making the current distribution of the negative electrode sheet more uniform, solving the problem of uneven current in the negative electrode sheet caused by zinc dendrites, and being able to fully utilize the negative electrode active material of the negative electrode sheet; the negative electrode sheet with added chopped aluminum silicate fibers and chopped carbon conductive fibers can take into account the long-term storage performance and cycle life performance of the nickel-zinc secondary battery, thereby improving the long-term storage performance and cycle life performance of the nickel-zinc secondary battery.
[0098] According to the 5-day-SOC, 10-day-SOC, 15-day-SOC and 150cyc-SOH of the comparative example in Table 1 and Examples 3-5, short-cut carbon conductive fibers are added to the negative electrode material on the basis of short-cut aluminum silicate fibers. The addition of short-cut carbon conductive fibers can significantly improve the cycle life performance of nickel-zinc secondary batteries.
[0099] According to the comparative example in Table 1 and 1C, 3C, 5C, and 10C of Examples 1-3, 6-7, the chopped aluminum silicate fibers are insulating materials. Adding chopped aluminum silicate fibers to the negative electrode material will affect the rate performance of the negative electrode and reduce the rate discharge performance of the nickel-zinc secondary battery. According to the 5-day-SOC, 10-day-SOC, 15-day-SOC and 150cyc-SOH, as well as 1C, 3C, 5C, and 10C of Examples 3-5, chopped carbon conductive fibers are added to the negative electrode material on the basis of adding chopped aluminum silicate fibers. Although the 5-day-SOC, 10-day-SOC, and 15-day-SOC of the nickel-zinc secondary battery are reduced, and the long-term storage performance of the nickel-zinc secondary battery is reduced, the 150cyc-SOH and 1C, 3C, 5C, and 10C of the nickel-zinc secondary battery can be improved, and the rate discharge performance and cycle life performance of the nickel-zinc secondary battery can be improved. Through the mutual cooperation of chopped aluminum silicate fibers and chopped carbon conductive fibers, the discharge capacity under high-rate discharge conditions can be significantly improved, thereby effectively meeting the requirements of the nickel-zinc secondary battery for high-rate discharge performance.
[0100] According to the 5-day-SOC, 10-day-SOC, 15-day-SOC and 150 cyc-SOH of Examples 4, 8 and 9 in Table 3, the chemical formula of the aluminum silicate of the chopped aluminum silicate fibers is Al X Si Y O (3 / 2X+2Y) Or XAl2O3·YSiO2, the silicon precipitated in aluminum silicate can form a very thin silica sol protective film on the surface of the electrode, which can inhibit the generation of zincate, thereby slowing down the side reaction between the negative electrode and the alkaline electrolyte and improving the SOC capacity. According to the data in Table 3, the chopped aluminum silicate fiber with X:Y=3:2 can be preferred.
[0101] According to the 5-day-SOC, 10-day-SOC, 15-day-SOC and 150cyc-SOH of Examples 3-5 in Table 1 and Examples 10-13 in Table 4, adding chopped carbon conductive fibers on the basis of adding chopped aluminum silicate fibers to the negative electrode material reduces the 5-day-SOC, 10-day-SOC and 15-day-SOC of the nickel-zinc secondary battery, and reduces the long-term storage performance of the nickel-zinc secondary battery. However, adding 1%-2% of chopped carbon conductive fibers to the negative electrode material can increase the 150cyc-SOH of the nickel-zinc secondary battery and improve the cycle life performance of the nickel-zinc secondary battery. The cycle life performance of the nickel-zinc secondary battery can be significantly improved by the mutual cooperation of chopped aluminum silicate fibers and chopped carbon conductive fibers. However, only adding chopped carbon conductive fibers to the negative electrode material cannot significantly improve the long-term storage performance and cycle life performance of the nickel-zinc secondary battery.
[0102] According to the data of the comparative example in Table 1 and Examples 14-18 in Table 5, if the chopped fibers are too short (the fiber length of the chopped fibers is less than or equal to 0.05 mm), the toughness and strength of the negative electrode sheet cannot be enhanced, and the role of preventing powder from falling off and building a conductive network cannot be played. During the storage and charge-discharge cycle process, the long-term storage performance and cycle life performance of the nickel-zinc secondary battery are not significantly improved; if the chopped fibers are too long (the fiber length of the chopped fibers is greater than or equal to 2.0 mm), during the preparation process of the negative electrode slurry, the excessively long chopped aluminum silicate fibers and chopped carbon conductive fibers are easily entangled and agglomerated on the stirring paddle, resulting in the inability to obtain a slurry containing the set mass percentage of chopped aluminum silicate fibers and chopped carbon conductive fibers, and the toughness and strength of the negative electrode sheet cannot be enhanced, and the role of preventing powder from falling off and building a conductive network cannot be played. If the chopped fibers are too long, the long-term storage performance and cycle life performance of the nickel-zinc secondary battery cannot be significantly improved; therefore, the fiber length of the chopped aluminum silicate fibers and the chopped carbon conductive fibers is 0.1 mm-1 mm, and the preferred fiber length is 1 mm.
[0103] The embodiments of the present application have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or improvements to the technology in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.
Claims
1. A negative electrode plate for a nickel-zinc secondary battery, characterized in that: It includes a negative electrode substrate and a negative electrode material coated on the negative electrode substrate; wherein, The negative electrode material includes a negative electrode active material, a surfactant, a binder, and chopped fibers; The fiber length of the chopped fibers is 0.1 mm to 1 mm, and the chopped fibers include chopped aluminum silicate fibers; The mass percentage of the chopped aluminosilicate fiber in the negative electrode material is 1%-3%; the chemical formula of aluminosilicate of the chopped aluminosilicate fiber is Al X Si Y O (3 / 2X+2Y) or XAl2O3·YSiO2, where 0 < Y ≤ X, and the ratio of X to Y, X∶Y = 1∶1, or 4∶1, or 3∶2.
2. The negative electrode plate of the nickel-zinc secondary battery according to claim 1, characterized in that: The chopped fibers further include chopped carbon conductive fibers, and the mass percentage of the chopped carbon conductive fibers in the negative electrode material is 1%-2%.
3. The negative electrode plate of a nickel-zinc secondary battery according to claim 1 or 2, characterized in that: The fiber diameter of the chopped fibers is 10 μm-20 μm.
4. The negative electrode plate of a nickel-zinc secondary battery according to claim 1, characterized in that: The negative electrode material also includes additives, which include Ca(OH)2, Bi2O3, and In2O3; the negative electrode active material includes spherical ZnO powder and Zn nanopowder; wherein, The mass percentage of the spherical ZnO powder in the negative electrode material is 55%-60%; The mass percentage of the Zn nanopowder in the negative electrode material is 5%-10%; The mass percentage of Ca(OH)2 in the negative electrode material is 1%-1.5%; The mass percentage of Bi2O3 in the negative electrode material is 0.5%-2%; The mass percentage of In2O3 in the negative electrode material is 0.05%-0.08%.
5. The negative electrode plate of the nickel-zinc secondary battery according to claim 1, characterized in that: The negative electrode substrate is a copper-tinned inclined wire mesh substrate.
6. A nickel-zinc secondary battery, characterized in that: The invention comprises a positive electrode plate, a separator and a negative electrode plate of a nickel-zinc secondary battery as claimed in any one of claims 1 to 5.
Citation Information
Patent Citations
Carbon fiber zinc negative electrode
CN102484246A